Thermal Cure Kinetics of Modified Cold-Setting Melamine-Urea-Formaldehyde Resins with Liquid Thickeners (Journal of Research Updates in Polymer Science, 2024)
Cold-setting melamine-urea-formaldehyde (CS-MUF) resins being used as adhesives for manufacturing laminated wood timber products require to have a proper viscosity using thickener or filler. However, studies on thermal curing kinetics and behavior of the modified CS-MUF resins with liquid thickener are limited. Hence, this study focuses on the thermal cure kinetics of the modified CS-MUF resins with two liquid thickeners at three addition levels to obtain the resin viscosities of 4,000 mPa.s, 8,000 mPa.s and 12,000 mPa.s. Differential scanning calorimetry (DSC) was used to estimate cure kinetics of the modified CS-MUF resins using two analysis methods: 1) model-fitting (MFT) method containing the Kissinger (KSNG) analysis, and 2) model-free (MFK) methods containing Kissinger-Akahira-Sunose (KAS) analysis, and nonlinear isoconversional (VYA) analysis. The KSNG, KAS, and VYA analysis showed that all modified CS-MUF resins followed very similar curing behavior with small difference, except Resin #2 which followed the autocatalytic reaction model based on the Málek method. These results suggest that liquid thickeners increase to a proper viscosity of CS-MUF resins without major impact to their curing behavior.